Development of proactive mode of providing tax deductions for personal income tax - E. L. Gulkova; M. V. Karp; M. V. Tipalina (Вестник университета)
The paper studies discussion issues of the simplified procedure for obtaining tax deductions for personal income tax (hereinafter referred to as PIT). The objectives of the study are the following: to review the changes in tax legislation from January 1, 2024 in the field of proactive mode of granting tax deductions for PIT, to justify the increasing role of this interaction between individuals and tax authorities, to identify current problems and to search for ways of solving them. The authors analysed the practice of application of the simplified procedure for obtaining property and investment tax deductions; statistical data of the Federal Tax Service of Russia on the provision of tax deductions in a simplified manner (1-DDK statistical form “On the declaration of personal income”). The analysis of key changes in the provision of deductions entering into force on January 1, 20124 was also conducted. The main problems that individuals may have when receiving deductions or that tax authorities may face in the course of tax control are highlighted, and possible ways to solve them are identified. The authors concluded, firstly, that it is necessary to form prefilled applications not only while receiving tax deductions, but also when paying PIT, for example, when a person sells real estate, cars. Secondly, it is required to enshrine in tax legislation the order of priority of providing tax deductions if a taxpayer has the right for several types of them. The obtained results can be used in developing solutions to taxation of personal income and provision of tax deductions, in legislative drafting on improvement of provisions of the state tax policy.